Are we too reluctant about irrational nutraceutical combinations? - Krishnan, V.; Murugaiah, Prakash; Bachmann, Aruna Maria (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The objective of the study was to study the rationality of Vitamins and minerals combinations available in India and to provide comprehensive data of irrational combinations having excess and sub sufficient quantity of vitamin and minerals than recommended by National Guidelines of India. Methods: This observational study and analysis was done between June and August 2016. Data was collected from current index of medical specialties and drug India. Rationality assessment was done using National list approved drug combinations by Central drug standard control organization (CDSCO) and essentially was cross checked using World Health Organization essential drug list 2015. Adequacy was analysed using Dietary reference intake (DRI) for Indians by Nutrional council of India draft guidance. Results: In our analysis, we have found 1184 irrational nutraceutical preparations available in India market. Out of 461(38.9%) are based on fat soluble vitamins, 190 (16.4%) based on B-complex vitamins based and 5339 (45.1%) related to essential minerals. Among 461 fat soluble vitamins, 104 contain excessive level, 334 contain substandard levels. Similarly 128 and 62 Vitamin B-Complex based preparations are having excess and less quantity than recommended levels respectively and almost all the mineral combinations except four are not prepared following guidelines. None of these combinations were included in National essential list of medicines. Conclusions: Multivitamins are generally considered safe; these are irrationally prescribed and taken as self-medication by public. Many of the ill effects are often unnoticed and under reported. Government of India should regulate the manufacture and sale these nutraceuticals to promote rational use of drugs and to promote wellbeing and safety of Indian population which is primary objective of ‘Health for all’.